Resiliency among secondary school students in Malaysia: assessment of the measurement model - Abu Bakar, A. (Time Taylor Academic Journals, 2010)
Some adolescents could successfully adapt with exposed risks and they are identified as resilient. Students identified as resilient are those who can successfully adapt with exposed risks. Resiliency is related to the individual quality or strength that increases his/her ability to withstand adversity (Holmes, 2006). A resilient person has also been described as one who commonly displays social competence, problem solving skills, optimism, invulnerability and person-environment fit (Brown et al, 2001; Kaplan, 2000). This paper makes an attempt to validate empirically the measurement model of adolescent resiliency using structural equation modeling (SEM). The adolescents? conceptions of resiliency measured such dimensions as active skills, future orientation, and risk taking and independence. This study was done to validate the Resiliency Belief Scales (Mrazek & Mrazek, 1987) based on a total sample of 308 secondary school students from east-coast of peninsular Malaysia. Cross-validation of the Resiliency Belief Scales (RBS) was done using a sub-sample of 148 students. . The Resiliency Belief Scales which was adapted from (Trammel, 2003), was used in this study. The instrument consisted of 45 items and the items were hypothesized a priori to have non-zero loadings on all dimensions in the model. Analysis of the items resulted in a well-fitting model (Ï‡2 = 1.327; df = 1; GFI = .998; CFI = .996; RMSEA = .03).